'Everyman his own historian': historical thinking and life history narration. Issue 1 (2nd January 2020) - Heuer, Christian
ABSTRACT: Historical thinking and historical learning face great challenges in our present times of permanent uncertainty. How can it be possible to make sense and provide orientation through historical narration in times when there seems to be no more security? In order to answer this question, I try to show, by means of contemporary autobiographical narratives, in their form as specific historical narratives for someone, how historical thinking in late modernity can help to orientate oneself as a narrative self in this uncertainty, but at the same time to insure oneself productively permanently against this uncertainty.